Forest based data collection in MR-MC wireless sensor networks - Wei-ping ZHANG; Ya-hong GUO; Meng WANG; Lin-yu NI; Jin-bao LI (Tongxin xuebao)
The limit of node itself and deployment environment of WSN result in the node was prone to failure and diffi-cult to maintain.In the tree-based data collection process,the node failure or lin congestion could result in higher com-munication delay,or even data loss.To solve this problem,a strategy for data collection was proposed which used forest as the routing structure.Firstly,an algorithm for the construction of forest was proposed,and then collect data through trees in the forest.Theoretical analysis and simulation results show that,the method could reduce the loss of data in the data collection process effectively,in the case of 25 fault nodes,the amount of data collected by forest routing structure of 3 trees compared to the amount of data collected from the connected dominating set is more than 55%,and reduce the la-tency of data collection.